If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2 = -3 + 2x Reorder the terms: 2 + 8x = -3 + 2x Solving 2 + 8x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 8x + -2x = -3 + 2x + -2x Combine like terms: 8x + -2x = 6x 2 + 6x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 6x = -3 + 0 2 + 6x = -3 Add '-2' to each side of the equation. 2 + -2 + 6x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = -3 + -2 6x = -3 + -2 Combine like terms: -3 + -2 = -5 6x = -5 Divide each side by '6'. x = -0.8333333333 Simplifying x = -0.8333333333
| 5x^2+8x-3=4 | | 90=2x+(x-15)2 | | 7x-7=-2x-10 | | (2x)+(3x-10)=70 | | 3x^2+5x+3=4 | | -9y-5=88+6y | | (6x-14)=(30x+54)+28 | | y=3/5x-4 | | 2x+1-3+x=10-2x | | 2*8+8y=64 | | 2x+8*0=64 | | 1/64x3 | | 2*0+8y=64 | | 1.10+.50x=9.10 | | 1/7+2/3 | | x=10+(-2y) | | 4^-8/4^-6 | | 30=16+(1)(5)x | | 2x+6=4+8x | | y=3*1-2 | | 32+m=150 | | 8x=4x+32 | | (7x)+(3x+20)=360 | | x^2+4x+4=-2 | | 5x+8+6=33 | | 6x^3+8x^2-4x=0 | | -4+8+(+2)+6= | | 8y+5-5y=1+2y-2 | | 8n-3=-19 | | 4x+2y+x=2y-x | | 3x-4=6+8x | | (X)(2)+13=20 |